If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -5(x + 1) = -3(2x + 3) Reorder the terms: -2x + -5(1 + x) = -3(2x + 3) -2x + (1 * -5 + x * -5) = -3(2x + 3) -2x + (-5 + -5x) = -3(2x + 3) Reorder the terms: -5 + -2x + -5x = -3(2x + 3) Combine like terms: -2x + -5x = -7x -5 + -7x = -3(2x + 3) Reorder the terms: -5 + -7x = -3(3 + 2x) -5 + -7x = (3 * -3 + 2x * -3) -5 + -7x = (-9 + -6x) Solving -5 + -7x = -9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -5 + -7x + 6x = -9 + -6x + 6x Combine like terms: -7x + 6x = -1x -5 + -1x = -9 + -6x + 6x Combine like terms: -6x + 6x = 0 -5 + -1x = -9 + 0 -5 + -1x = -9 Add '5' to each side of the equation. -5 + 5 + -1x = -9 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = -9 + 5 -1x = -9 + 5 Combine like terms: -9 + 5 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| x/2=18 | | 15(x-4)=60 | | 15-3r=-45 | | 14(x-4)=60 | | 13(x-4)=60 | | 2+4+x=5+1 | | 12(x-4)=60 | | 7x+6=.50(2x-8) | | 11(x-4)=60 | | 8(x-4)=60 | | 8(63-y)+4y=254 | | (8/7)x-8=6x-4y | | 12-(3x-7)=4-x | | 0=x+8 | | 0.8x=320 | | 3(5x-1)-14x=4 | | 14=3+x | | -36-9y+18=-34y+12+15y | | 4s-1=2-2s | | 10(x-4)=60 | | -a+7=17+3a-4 | | x+3y=80 | | 15+216-315-16= | | 4(y-7)/3=-2y | | -8+7x+9=3x-43 | | 0.4z+0.7=-3.5-1.7z | | 5X+4Y+z=200 | | -4(x-5)+2=22 | | 9+(2x+5)=3(2x+4) | | 1.2+0.3x=0.5x-3.2 | | -9x^4=-48x^2+64 | | 0.5x-2+5= |